The long, hot summer [videorecording (DVD)] - North, Alex (Twentieth Century Fox Home Entertainment, 2003)
Ben Quick, an industrious con artist who's known throughout the country as a barn burner, gets run out of a Mississippi town. He meets up with Clara Varner, whose father is pressuring her to get married and provide him with grandchildren. It isn't long before he decides Ben and Clara should marry, and when she resists, it sets up a dramatically escalating clash of wills.